Correlation of Postural Asymmetries with Gross Motor Functional Classification among Cerebral Palsy Children - Somia Faisal; Amal Shakeel; Samreen Sadiq; Hafiz Muhammad Asim; Amer Aziz (Pakistan journal of medicine and dentistry, 2024)
Background: Motor control and posture disorders are responsible in the development of cerebral palsy (CP). Spastic CP, the most common type of CP is associated with postural asymmetries resulting in functional limitation among children and compromising their quality of life. Therefore, the study aimed to describe the severity of postural asymmetries among special school going children with spastic cerebral palsy in correlation with Gross Motor Function Classification System levels (GMFCS). Methods: Thirty-four subjects from Lahore who were special school going children diagnosed with spastic CP for more than 6 months and less than 1 year were recruited. Children with uncontrolled seizures, hearing and visual impairment, surgery scheduled and other types of cerebral palsy were excluded. The scale used for the assessment of postural asymmetries was Posture and Postural Ability Scale with the reliability of 0.99. ANOVA test was applied with p<0.05 considered as statistically significant. Results: Severe asymmetries were found in standing position with 5.9% (n=2) in frontal and 20.6% (n=7) in sagittal plane. There were mild asymmetries in supine position, 55.9% (n=19) in frontal and 50% (n=17) in sagittal plane. In prone position, reported asymmetries were 55.9% (n=19) in frontal and 44.1% (n=15) in sagittal plane. In sitting position 76.5% (n=26) accounted for both frontal and sagittal plane asymmetries. p<0.05 showed significant distribution of postural asymmetries. Conclusion: Severe postural asymmetries were found in standing position (p<0.05). However, high frequency of pain, scoliosis and hip dislocation were observed at level III of GMFCS among special school going children diagnosed with spastic cerebral palsy. Keywords: Cerebral Palsy; Children; Spastic; Muscle Spasticity.